PROVERBS IN AN AMERICAN MUSICAL: A COGNITIVE-DISCURSIVE STUDY OF “THE FULL MONTY” - Konstantinova, Anna (Proverbium - Yearbook, 2012)
In this article I present the results of the cognitive-discursive study into the way Anglo-American proverbs function in an American musical. “The Full Monty” was selected as the material for my analysis. First, I look at some characteristic features of the American musical dis-course relevant to the study. Next, I distinguish the functions proverbs fulfill in “The Full Monty” discourse. Last, I compare how proverbs are used both in the musical and the eponymous British movie.